Mifepristone alters APP processing to preclude Aβ and also reduces tau pathology - Baglietto-Vargas, David (2013)
BACKGROUND: Increased circulating glucocorticoids are features of both aging and Alzheimer’s disease (AD), and increased glucocorticoids accelerate the accumulation of AD pathologies. Here we analyzed the effects of the glucocorticoid receptor antagonist mifepristone (RU-486) in the 3xTg-AD mouse model at an age where hippocampal damage leads to high circulating corticosterone levels. METHODS: The effects of mifepristone were investigated in 3xTg-AD mice using a combination of biochemical, histological and behaviour analyses. RESULTS: Mifepristone treatment rescues the pathologically-induced cognitive impairments and markedly reduces Aβ-load and levels, as well as tau pathologies. Analysis of APP processing revealed concomitant decreases in both APP C-terminal fragments C99 and C83 but the appearance of a larger 17-kDa C-terminal fragment. Hence, mifepristone induces a novel C-terminal cleavage of APP that prevents it being cleaved by α- or β- secretase, thereby precluding Aβ generation in the CNS; this cleavage and the production of the 17-kDa APP fragment was generated by a calcium-dependent cysteine protease. In addition, mifepristone treatment also reduced the phosphorylation and accumulation of tau, concomitant with reductions in p25. Notably, deficits in CREB signaling were restored with the treatment. CONCLUSIONS: These preclinical results point to a potential therapeutic role for mifepristone as an effective treatment for AD and further highlight the impact the glucocorticoid system has as a regulator of Aβ generation.